Nursing Interventions Targeting Fatigue in Inflammatory Bowel Disease: A Systematic Review - Matteo Martinato; Elena Boffo; Greta Lorenzon; Eleonora Monaco; Clara Iervolino; Rosanna Irene Comoretto; Edoardo Vincenzo Savarino; Dario Gregori (Gastrointestinal Disorders)
A prevalent symptom among Inflammatory Bowel Disease (IBD) patients is fatigue, characterized by a persistent sense of energy depletion that affects all aspects of daily life. This review aims to evaluate nursing interventions reported in the literature to alleviate fatigue in IBD patients. A comprehensive search was conducted across four electronic databases—PubMed, CINAHL, Cochrane, and Scopus—and four scientific journals: “Gastroenterology”, “Inflammatory Bowel Disease”, “Journal of Crohn’s and Colitis”, and “United European Gastroenterology Journal”. Inclusion criteria were clinical trials involving adult IBD patients in remission or mild disease activity. Out of 234 studies, 2 were selected for review. These studies assess the effectiveness of Solution-Focused Therapy (SFT) that emphasizes solving problems and developing strategies for improvement, and Problem-Solving Therapy (PST) that focuses on identifying problems and coping strategies. SFT showed a positive impact on fatigue with a significant improvement in the Checklist Individual Strength after three months: 45.5% in the control group, 85.7% in the SFT group, and 60% in the PST group, but its impact declined over time. Additionally, SFT demonstrated potential for reducing healthcare costs compared to standard of care and PST. Further research is needed to provide nurses interventions for managing fatigue in IBD patients. The review protocol has been registered at OSF.io.